Oxidative Stress-Induced Misfolding and Inclusion Formation of Nrf2 and Keap1 - Vy Ngo; Nadun C. Karunatilleke; Anne Brickenden; Wing-Yiu Choy; Martin L. Duennwald (MDPI AG, 2022)
Cells that experience high levels of oxidative stress respond by inducing antioxidant proteins through activation of the protein transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2). Nrf2 is negatively regulated by the E3 ubiquitin ligase Kelch-like ECH-associated protein 1 (Keap1), which binds to Nrf2 to facilitate its ubiquitination and ensuing proteasomal degradation under basal conditions. Here, we studied protein folding and misfolding in Nrf2 and Keap1 in yeast, mammalian cells, and purified proteins under oxidative stress conditions. Both Nrf2 and Keap1 are susceptible to protein misfolding and inclusion formation upon oxidative stress. We propose that the intrinsically disordered regions within Nrf2 and the high cysteine content of Keap1 contribute to their oxidation and the ensuing misfolding. Our work reveals previously unexplored aspects of Nrf2 and Keap1 regulation and/or dysregulation by oxidation-induced protein misfolding.